Hip and upper extremity kinematics in youth baseball pitchers - Holt, T.; Oliver, G. D. (Journal of Sports Sciences, 2016)
The purpose of this study was to examine the relationship between dynamic hip rotational range of motion and upper extremity kinematics during baseball pitching. Thirty-one youth baseball pitchers (10.87 ± 0.92 years; 150.03 ± 5.48 cm; 44.83 ± 8.04 kg) participated. A strong correlation was found between stance hip rotation and scapular upward rotation at maximum shoulder external rotation (r = 0.531, P = 0.002) and at ball release (r = 0.536, P = 0.002). No statistically significant correlations were found between dynamic hip rotational range of motion and passive hip range of motion. Hip range of motion deficits can constrain pelvis rotation and limit energy generation in the lower extremities. Shoulder pathomechanics can then develop as greater responsibility is placed on the shoulder to generate the energy lost from the proximal segments, increasing risk of upper extremity injury. Additionally, it appears that passive seated measurements of hip range of motion may not accurately reflect the dynamic range of motion of the hips through the progression of the pitch cycle.